2021
DOI: 10.1590/1806-9282.20210414
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 findings in chest computed tomography

Abstract: OBJECTIVE:The aim of this study was to describe chest computed tomography image findings in patients with COVID-19. METHODS:The chest computed tomography scans of 453 hospitalized patients with confirmed COVID-19 were collected at two tertiary care Brazilian hospitals. Demographics and clinical data were extracted from the electronic record medical system. RESULTS:The main chest computed tomography findings were ground-glass opacities (92.5%), consolidation (79.2%), crazy-paving pattern (23.9%), parenchymal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
1
6
0
3
Order By: Relevance
“…The majority of the hospitalized patients diagnosed with COVID-19 were men, with a rate of 53%. This result is in parallel with the studies in which 57% were male (Calvi et al, 2021) and 52% were male (Yurdaisik et al, 2021). The most common symptoms in COVID-19 patients are fever, cough, and shortness of breath, but some of them can have the disease asymptomatically .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The majority of the hospitalized patients diagnosed with COVID-19 were men, with a rate of 53%. This result is in parallel with the studies in which 57% were male (Calvi et al, 2021) and 52% were male (Yurdaisik et al, 2021). The most common symptoms in COVID-19 patients are fever, cough, and shortness of breath, but some of them can have the disease asymptomatically .…”
Section: Resultssupporting
confidence: 84%
“…Most hospitalized patients had more than 25% pulmonary involvement. Also, most patients who died due to it had more than 50% pulmonary involvement, indicating a worse prognosis depending on the size of the affected area (Calvi et al, 2021). Toussie et al reported that patients with ground-glass opacity detected in at least two pulmonary areas were more likely to need hospitalization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of lung commitment is a predictive factor of greater severity and mortality. The most common tomographic findings in severe cases consist of ground-glass opacity (92.5%), consolidation (79.2%), parenchymal bands (50%), septal thickening (43.5%), mosaic paving pattern (23.9%) and inverted halo sign (3.5%) ( 23 ) . Although less sensitive than chest CT, X-rays are useful in assessing pneumonia, pleural effusion or pulmonary edema, and the most common abnormalities are consolidation (28%) and ground-glass opacities (29%).…”
Section: Discussionmentioning
confidence: 99%
“…( 28) En el presente estudio, la tomografía computarizada de tórax mostró una mayor sensibilidad que el ensayo, pero la sensibilidad fue solo del 73,3% entre los pacientes sintomáticos que dieron positivo para el SARS-CoV2 según RT-qPCR. (29) Bernheim y colaboradores, informó que la sensibilidad de la tomografía computarizada de tórax era baja (44%) en la fase aguda (0 a 2 días después del inicio) pero alta (91%) en la fase intermedia (3 a 5 días). La baja sensibilidad de la tomografía computarizada de tórax puede reflejar el corto período de tiempo entre el inicio de los síntomas y la hospitalización en los pacientes sintomáticos examinados en este estudio.…”
Section: Signos Vitalesunclassified